A facile and rapid preparation of highly crumpled nitrogen-doped graphene-like nanosheets for high-performance supercapacitors1. Issue 25 (7th July 2015) - Peng, Hui; Ma, Guofu; Sun, Kanjun; Zhang, Zhiguo; Yang, Qian; Ran, Feitian; Lei, Ziqiang
<x xml:space="preserve">Abstract</x> Highly crumpled nitrogen-doped graphene-like nanosheets (CN-GLSs) with a high specific surface area (1169 m2 g−1) and large pore volume (2.58 cm3 g−1) are prepared from a macroporous resin via simultaneous urea gasification expansion and CaCl2 activation methods.